Pengaruh Kompetensi Sumber Daya Manusia, Literasi Keuangan, dan Teknologi Media Sosial Terhadap Kinerja UMKM di Rawa Bendungan Cilacap - Ibnu Detri Kurniawan; M. Rijal Pemungkas; Mutia Pamikatsih; Hakim Hakim (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of Human Resource Competence, Financial Literacy, and Social Media Technology on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Rawa Bendungan, Cilacap. The background of this research is based on the importance of improving MSME performance as one of the driving sectors of the community's economy, which is influenced by the quality of human resources, financial management capabilities, and the utilization of digital technology in business activities.This study employed a quantitative approach using a survey method. The population consisted of MSME actors in Rawa Bendungan, Cilacap, with a sample of 85 respondents determined using a specific sampling technique. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis, including t-tests, F-tests, and the coefficient of determination (R²).The results show that partially and simultaneously, Human Resource Competence (X1), Financial Literacy (X2), and Social Media Technology (X3) have a positive and significant effect on MSME performance. The coefficient of determination (R²) is 76%, indicating that the independent variables explain 76% of the variation in MSME performance. The research model demonstrates that the three independent variables adequately explain the performance of MSMEs. Based on these findings, it is recommended that MSME actors continuously improve their competencies, enhance financial management practices, and optimize the use of social media technology to increase competitiveness and business sustainability. The government and related stakeholders are also expected to provide support through training programs, mentoring, and facilitation of access to financing.